2001
DOI: 10.1001/archinte.161.18.2205
|View full text |Cite
|
Sign up to set email alerts
|

Is "Isolated Home" Hypertension as Opposed to "Isolated Office" Hypertension a Sign of Greater Cardiovascular Risk?

Abstract: This retrospective analysis suggests that patients with isolated home hypertension belong to a high-risk subgroup. The 3-year follow-up of these patients will provide prospective data about the cardiovascular prognosis of these subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 31 publications
7
67
0
1
Order By: Relevance
“…This finding is probably related to the fact that masked hypertensives remain undiagnosed and untreated for a long period of time. 7,11,29 This view is supported by the fact that masked hypertensives received less antihypertensive treatment and combination treatment for hypertension than white coat or sustained hypertensives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is probably related to the fact that masked hypertensives remain undiagnosed and untreated for a long period of time. 7,11,29 This view is supported by the fact that masked hypertensives received less antihypertensive treatment and combination treatment for hypertension than white coat or sustained hypertensives.…”
Section: Discussionmentioning
confidence: 99%
“…9 A number of studies have shown the powerful prognostic value of ambulatory and home BP measurements in relation to cardiovascular morbidity and mortality. 1,7,11,12 The underlying mechanisms of MH remain unclear. There is evidence that this phenomenon is related with young age, male gender and smoking.…”
Section: Introductionmentioning
confidence: 99%
“…100,101 The frequency of white-coat hypertension based on home BP measurements has been reported to be 38-58% in cohorts of the general population, [102][103][104] 15% in untreated patients with hypertension 105 and 12-19% in hypertensive patients being treated. [106][107][108] The prognosis of white-coat hypertension depends on home BP levels. If high normal BP home measurements (125-135/ 80-85 mm Hg; see Chapter 9) are regarded as normal, the prognosis of white-coat hypertension tends to be poor.…”
Section: ) Measurement Of Home Bp Under Special Conditionsmentioning
confidence: 99%
“…The frequency of masked hypertension based on home BP is reported to be about 10% in cohorts of the general population 103,104 and 11-33% in hypertensive patients under treatment. 108,113,114 3. Morning hypertension, and morning and evening home BP Although there is no precise definition of morning hypertension, a condition with a specifically high BP after waking early in the morning may be referred to as morning hypertension.…”
Section: Masked Hypertensionmentioning
confidence: 99%
“…Of note, we found in our study an unexpected high rate of patients with isolated home BP at the end of the study. A cross-sectional study 28 has suggested these patients to be at a higher cardiovascular risk, as long as they have been found with more risk factors and a more frequent history of cardiovascular diseases, in comparison with other patients. However, we should have to wait for 3 years to know whether this hypothesis is confirmed or not, by a longitudinal approach.…”
Section: Comparison Of Office and Home Bp Measurementsmentioning
confidence: 99%